Assessing the reliability of noise simulation models in a built-up area - Sankov, Petro; Zakharov, Yuriy; Zakharov, Vadim; Тkach Nataliia (Academic journal Industrial Machine Building Civil Engineering, 2025)
In modern environments, noise is a dominant factor negatively impacting the urban ecosystem and, consequently, the health of city residents. Noise exposure reduces labor productivity and the efficiency of rest, serves as a primary cause of nervous disorders, and significantly diminishes the quality and safety of life. The aim of the study is to determine the reliability of developing simulation models for sound propagation in urban built-up areas. Research methods include field instrumental measurements, a cartographic method for predicting noise pollution from sources with the construction of 3D sound field models, and statistical methods for processing and evaluating research results. The results demonstrate a strong relationship between the outcomes of field instrumental measurements and the cartographic prediction of the noise regime in the studied residential area. The calculated correlation coefficient amounted to r = 0.889, indicating a high level of agreement between the compared datasets. In addition, the required number of observations to determine the degree of correlation between the two groups of compared sound level values was established as 12 observations